Watership Down - Adams, Richard, 1920- (New York, Macmillan, 1974)
Chronicles the adventures of a group of rabbits searching for a safe place to establish a new warren where they can live in peace.
Keywords: Rabbits -- Fiction; Rabbits -- Fiction